Subcutaneous ureteral bypass explantation in 21 cats (2015-2023): outcomes and owner perceptions - Sophie E Broughton; Anna Frykfors von Hekkel; Matteo Rossanese; Lynda Rutherford; Rebecca F Geddes; Jack S Lawson (Journal of Veterinary Internal Medicine, 2026)
Abstract Background Subcutaneous ureteral bypass (SUB) can be an effective treatment for ureteral obstruction in cats, but SUB explantation is little documented. Hypothesis/Objectives Describe reasons for SUB explantation, outcomes, and owner experiences. We hypothesized that explantation would be effective in managing common SUB-related complications. Animals Twenty-one cats (31 SUBs) that underwent 29 explantations. Methods Retrospective case-series of cats undergoing explantation between 2015 and 2023 with medical record review and 20 owners emailed for follow-up. Results are median (range). Results Explantation was performed 1.8 years (0.2-4.1 years) after placement because of positive urine culture (PUC; 15/21), SUB obstruction (8/21), sterile cystitis (4/21), and suspected SUB failure (2/21). Twenty-six out of 31 ureters had documented patency. Seventeen cats had all implants removed (9 unilateral, 8 bilateral). Two underwent unilateral explantation and ipsilateral ureteronephrectomy. Two with bilateral SUBs underwent unilateral explantation. Follow-up after explantation was 596 days (3-2310 days). Four cats had ureteral re-obstruction (1 after partial obstruction at explantation), 10 did not re-obstruct and the remainder were undetermined. Seven cats died at 614 days (405-2200 days), 11 were lost to follow-up at 135 days (19-1774 days) after explantation, and 3 remained alive. Four deaths were renal related (2/4 re-obstructions). Nine of 15 cats explanted due to PUC had a negative postoperative urine culture. Three of 15 cats had clinical signs related to PUC postoperatively. Questionnaire response was 9 of 20, and 8 of 9 owners would consider explantation if in the same situation again. Conclusions and clinical importance For SUB cats with complications, explantation is a viable option. A small proportion of cats had clinical signs of PUC, or ureteral re-obstruction postoperatively.